KUASA HUKUM ADAT ORANG ASLI PAPUA (OAP) TERHADAP PENDATANG DI KOTA SORONG, PAPUA BARAT - Udin Latif; Hermanto Hermanto; Rusyaid Rusyaid; Husni Kamaluddin; Alda Amris (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service-based research aims to find out the application of customary law for immigrant communities in Sorong City, identify and find stakeholder efforts towards the application of customary law for immigrant communities in Sorong City. This service-based research was carried out in the city of Sorong, with the type of research assistance using the Participation Action Research (PAR) approach. The assisted object is the Bugis Tribe as one of the Migrant Tribes. The Bugis tribe is one of the tribes in Sorong City which is often the perpetrators and victims of OAP. Owned Resources are KKM Bone Management and the Bone Community in Sorong City. The parties involved in this research were the Research Team, Head of Traditional Actors and Victims, Sorong City Religious Leaders, and Sorong City Community Leaders. The results of this devotion-based research show: First, the application of OAP customary law for immigrant communities in Sorong City is paying fines to victims of OAP in the form of money agreed upon by the traditional leaders of both parties and facilitated and witnessed by the Police. Pay the fine as a form of restriction, protection and self-esteem for OAP. Second, the efforts of stakeholders towards the application of customary law for immigrant communities in Sorong City are carrying out socialization activities for Papuan customary law, workshops on Papuan customary law, and prevention activities.